219k views
5 votes
Pleaseee Helpp!!!

Given: In △ABC, AD ⊥ BC Prove: What is the missing statement in Step 6? a. b = c b. h/b=h/c C. csin(B) = bsin(C) D. bsin(B) = csin(C)

Pleaseee Helpp!!! Given: In △ABC, AD ⊥ BC Prove: What is the missing statement in-example-1
User Grantespo
by
6.0k points

2 Answers

3 votes

In step 6 we substitute the value we just found for h in step 5 into the equation in step 3. That's also an equation for h, so we're just setting the other sides equal:



c \sin B = b \sin C


Third choice.



User Dstibbe
by
5.6k points
1 vote

Answer:

Given: In ΔABC ,
AD \perp BC

To prove that:
(\sin B)/(b) =(\sin C)/(c)


AD \perp BC [Given]

In ΔADB

The sine angle is defined in the context of a right triangle is the ratio of the length of the side that is opposite that angle to the length of the longest side of the triangle.


\sin B =(h)/(c) [By definition of sine] .....[1]

Multiplication Property of equality states that you multiply both sides of an equation by the same number.

Multiply by c to both sides of an equation [1] we get;


c \cdot \sin B =c \cdot(h)/(c)

Simplify:


c \sin B = h ......[2]

Now, In ΔACD

Using definition of sine:


\sin C =(h)/(b)

Multiply both sides of an equation by b;


b \cdot \sin C = b \cdot (h)/(b) [Multiplication Property of equality]

Simplify:


b \sin C = h ......[3]

Substitute [3] in [2];


c \sin B = b \sin C ......[4]

Division property of equality states that if you divide both sides of an equation by the same nonzero number the sides remains equal.

[4] ⇒
(\sin B)/(b) =(\sin C)/(c)

Therefore, the missing statement in step 6 is;
c \sin B = b \sin C



Pleaseee Helpp!!! Given: In △ABC, AD ⊥ BC Prove: What is the missing statement in-example-1
User Marcell Erasmus
by
5.5k points